PENGARUH VARIABEL MAKRO TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI 5 NEGARA ASEAN - Ristina Tina (MUSLIMPRENEUR : Jurnal Ekonomi dan Kajian Keislaman, 2021)
This study is aimed to determine the progress of stock market in ASEAN after financial crisis in 2008. Stock market performance is measured based on impacts of macroeconomic such as (inflation, exchange rates (kurs) and interest rates). This study uses a composite stock price index as the dependent variable in 5 ASEAN countries (Indonesia, Malaysia, Singapore, Thailand, and Philippines). This research used panel data regression methods with the fixed effect mode approach with observation period of 2014-2019. The results of this study indicate that the stock markets in 5 ASEAN countries are significantly affected by macroeconomic conditions such as inflation, exchange rates (exchange rates) and interest rates.